Association of maternal and cord plasma total, free and bioavailable 25-hyrodroxyvitamin D with neonatal anthropometric measurements at birth: a preliminary study in a private hospital - Lee, Siew Siew; Loh, Su Peng; Subramaniam, Raman; Tusimin, Maiza; Ling, King Hwa; Rahim, Kartini Farah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: 25-hydroxyvitamin D (25OHD) is the principal biomarker of vitamin D status. In circulation, 25OHD is primarily bound to vitamin D binding protein (VDBP), leaving a small proportion bound to albumin and as free form. Previous studies have suggested that free 25OHD is better correlated with health outcomes. However, in pregnancy where VDBP level is extremely elevated, the correlations between free 25OHD with health outcomes are far from conclusive. Here we show the associations of maternal and cord total, free and bioavailable 25OHD con-currently with neonatal anthropometric measurements in healthy pregnant mothers-neonates pairs. Method: Total 25OHD level was measured by using chemiluminescent immunoassay. Free and bioavailable 25OHD were calculated using published mathematical models. Results: The results showed that birth weight and head circumference were negatively associated with maternal total 25OHD but not significantly associated with free and bioavailable 25OHD. There were no significant associations between cord total, free and bioavailable 25OHD with any of the neonatal anthropometric measurements. Conclusion: The outcomes of this study should encourage further research in a larger sample size. Notably, future research could lead to the establishment of causative relationships and plausible mechanisms between maternal and cord 25OHD with neonatal anthropometric measurements.